2013
DOI: 10.1016/j.applanim.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences modulate stress coping in a population of German shepherd dogs

Abstract: Early experiences may alter later behavioural expressions in animals and these differences can be consistent through adulthood. In dogs, this may have a profound impact on welfare and working ability and, it is therefore interesting to evaluate how experiences during the first weeks of life contribute to shaping the long-term behaviour. We analysed data from 503 dogs from 105 litters, bred at the Swedish Armed Forces Dog Kennel. For each dog, the data comprised information on dam and sire, sex, litter size, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 46 publications
(49 reference statements)
4
52
2
1
Order By: Relevance
“…Other factors, such as litter size and season of birth, could also predict some elements of adult behaviour (Foyer et al, 2013). Physical engagement, i.e., interest in objects and better retrieval skills, are more pronounced in 1-2-yearold dogs born during the harsh winter time.…”
Section: The Predictive Significance Of Puppy Testingmentioning
confidence: 99%
“…Other factors, such as litter size and season of birth, could also predict some elements of adult behaviour (Foyer et al, 2013). Physical engagement, i.e., interest in objects and better retrieval skills, are more pronounced in 1-2-yearold dogs born during the harsh winter time.…”
Section: The Predictive Significance Of Puppy Testingmentioning
confidence: 99%
“…Evaluation of the records of German shepherd dogs from the Swedish armed forces demonstrated that puppies from more experienced bitches scored better for confidence and physical engagement, based on principal component analyses, when tested as young adult dogs (Foyer et al . ). In contrast, in a study using bitches from a guide dog facility, mothers who whelped fewer litters had significantly higher maternal behaviour scores than more experienced mothers (Bray et al .…”
Section: Factors Influencing Maternal Behaviourmentioning
confidence: 97%
“…However, since it was demonstrated that adult dogs' character traits can be affected by maternal, litter‐related and seasonal variables experienced early in life (Foyer et al . ), a considerable amount of available data has been published in this area (Guardini et al . , Czerwinski et al .…”
Section: Introductionmentioning
confidence: 99%
“…We have found that the results of dogs in a very similar type of behavioural test reflect quality and quantity of maternal care received during the first weeks of life (Foyer et al, 2015;2013), which may be related to genetic differences between mothers.…”
Section: Assessing Dog Behaviourmentioning
confidence: 98%